The fit between product market strategy and business model: implications for firm performance - Zott, Christoph; Amit, Raphael (Strategic Management Journal, 2008)
Abstract We examine the fit between a firm's product market strategy and its business model. We develop a formal model in order to analyze the contingent effects of product market strategy and business model choices on firm performance. We investigate a unique, manually collected dataset, and find that novelty‐centered business models—coupled with product market strategies that emphasize differentiation, cost leadership, or early market entry—can enhance firm performance. Our data suggest that business model and product market strategy are complements, not substitutes. Copyright © 2007 John Wiley & Sons, Ltd.